Nasoendoscopic findings after primary palatal surgery: Can the Furlow technique result in a smaller velopharyngeal gap? - Ferreira, Gabriela Zuin; Dutka, Jeniffer de Cássia Rillo; Whitaker, Melina Evangelista; de Souza, Olivia Mesquita Vieira; Marino, Viviane Cristina de Castro [UNESP]; Pegoraro-Krook, Maria Inês (FapUNIFESP (SciELO), 2015)
Purpose: To compare the nasoendoscopic findings related to the velopharyngeal gap among patients with cleft palate who underwent the Furlow (F) technique and those who underwent the von Langenbeck (vL) technique for primary palatal surgery, who remained with velopharyngeal insufficiency (VPI). Methods: The analyzed data were retrieved from the institution's data of recordings of nasoendoscopic exams. The sample comprised 70 recorded nasoendoscopic exams obtained from 22 patients who underwent the F technique and from 48 who underwent the vL technique during primary palatoplasty, who remained with VPI after surgery and were submitted to nasoendoscopy, between the ages of 5 and 15 years (mean age: 8 years), for definition of the best treatment for VPI. The images were edited into a DVD in a randomized sequence to be assessed by three experienced speech language pathologists regarding displacement and excursion of the soft palate; displacement and excursion of lateral pharyngeal's walls; displacement and excursion of the posterior pharyngeal's wall; and presence of the Passavant ridge and size and type of velopharyngeal gap. Results: The results of the comparison of measurements between F and vL groups were not statistically significant. Conclusion: The surgical technique used in primary palatoplasty was not relevant to determine the difference in the size of the velopharyngeal gap for patients who maintained VPI.
Keywords: Cleft palate; Evaluation; General surgery; Speech; Velopharyngeal insufficiency